The hsa_circ_0039857/miR-338-3p/RAB32 axis promotes the malignant progression of colorectal cancer - Pei Xu; Siying Cheng; Xianwei Wang; Shuming Jiang; Xiaoyan He; Lina Tang; Ning Wu; Zhirong Yang (BMC Gastroenterology, 2022)
Abstract Background Colorectal cancer (CRC) is a prevalent malignancy of the gastrointestinal. Circular RNAs (circRNAs) act as important roles in CRC malignant progression. However, the role of circ_0039857 in CRC is still unclear. Therefore, this study aimed to explore the function and mechanism of hsa_circ_0039857 in the CRC. Methods The mRNA and protein expression were measured via RT-qPCR. RNase R assay and Actinomycin D were employed to evaluate the stability of circ_0039857. Functional experiments, such as proliferation and apoptosis, were applied to study the function of circ_0039857 in CRC cells. The underlying mechanisms of circ_0039857 were then analyzed by bioinformatics, dual-luciferase reporter gene assay, RNA pull-down and rescue experiments. Results We revealed that circ_0039857 was significantly enhanced in CRC. Circ_0039857 was stabler than linear RNA in cells and valuable for the disease diagnosis. In addition, circ_0039857 knockdown inhibited proliferation and promoted apoptosis. Mechanistically, circ_0039857 positively regulated the expression of RAB32 via sponging miR-338-3p. Conclusion This study demonstrated that circ_0039857 knockdown suppressed CRC malignant progression through miR-338-3p/RAB32 axis. Most importantly, this will help us to better understand the circRNA network in CRC, and may find potential biomarkers and targets for CRC clinical treatment.